Analisis Faktor Makroekonomi Terhadap Pertumbuhan Perekonomian Di Indonesia - Prayitno, Andaru Rachmaning Dias; Muh. Imaduddin Akbar; Maula Fadhilata Rahmatika (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of key macroeconomic factors, namely interest rate (BI Rate), Rupiah/USD exchange rate, and inflation on Indonesia's economic growth during the 2011–2019 period. The research method used is quantitative with a linear regression analysis approach using quarterly time-series data. The model was estimated using the Ordinary Least Squares (OLS) method after passing classical assumption tests. The results show that simultaneously, all three variables have a significant effect on economic growth. However, partially, only interest rate and exchange rate show significant negative impacts, where a 1% increase in each variable reduces economic growth by 0.13% and 2.06%, respectively. Inflation has no significant effect, likely due to its relative stability during the observation period. The study concludes that interest rate and exchange rate are consistent macroeconomic factors influencing Indonesia's economic growth performance before the pandemic period.